The grammar is ambiguous. The word $abbabb$ can be derived in at least 3 ways:
$$S \Rightarrow SaSMSM \Rightarrow^2 SaMM \Rightarrow SaSMSMaMM \Rightarrow^7 abbabb,$$
$$S \Rightarrow SaSMSM \Rightarrow^2 aSMM \Rightarrow aSMSMSaMM \Rightarrow^7 abbabb,$$
$$S \Rightarrow SaSMSM \Rightarrow^2 aMSM \Rightarrow aMSMSaSMM \Rightarrow^7 abbabb.$$
I found this by thinking about how words in the language might be parsed. My first observation was that if a word ends with $a$, the derivation must have started with the last rule for $S$. If it ends with $b$ or $c$ one of the other non-$\epsilon$-rules must have been used in the first step.
In order to distinguish these two rules, I looked at the preceding symbol, which is $S$ for both rules. The symbol before that differs again. So if we could uniquely identify the word resulting from the $S$ we could determine the initial rule unambiguously. If we furthermore could uniquely identify which subword results from which symbol of the rule in each case, we would get a procedure that yields a unique parse tree for each word, proving unambiguity.
Alas, I noted that it is not possible to uniquely determine the yield of the rightmost $S$. But now I had a better idea, how an ambiguous word should look like.